Comparative study of passive magnetic bearing using four ring magnets: a critical review - Chaojun, Yang; Wondimu, Amberbir; Salau, Ayodeji Olalekan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Researchers on reducing energy losses caused by friction in small-scale wind turbines. This is crucial because a significant amount of energy is wasted due to friction in the main roller bearing. In order to overcome this, the concept of levitation has gained popularity. Levitation is achieved by employing the repelling forces between two opposing poles of a permanent magnet (PM), significantly reducing friction between the turbine stator and rotor. As a result, the overall energy production of the turbine increases. The use of passive permanent magnet bearings has several disadvantages, such as limited load-bearing capacity and rigidity. To address these limitations, we conducted numerical studies on four different configurations in order to enhance load-bearing capacity and stiffness. The results showed that the radial configuration outperformed the axial-type configuration in terms of stiffness and load-bearing capabilities in all four arrangements. Furthermore, it was revealed that radial passive magnetic bearings with adequate air gaps are not only more efficient but also less expensive than employing iron cores at the rear and between ring magnets for small-scale wind turbines.